Perfecting the art of doing... nothing! / Isma Noornisa Ismail - Ismail, Isma Noornisa (Academy of Language Studies, 2023)
Have you finished marking your students' essays? How about the article for our next webinar? Have you completed the revision for the Scopus paper? The due date for FRGS application is tomorrow and is your proposal ready? If you are my colleague, these questions are our 'normal' greetings to one another. Whether we realize it or not, work occupies a large segment of our daily time that we barely have time to squeeze in for any other activities. If you think that keeping busy is good, think again, as it is actually counterproductive! This 'hustle' culture is unfortunately damaging not only our physical being, but our mental health as well. Anxiety and depression are reported to be increasing, along with the pressure to always be productive. If you do not want to drown in work and lose your sense of identity, read on. Let's discover the ancient art of doing NOTHING. If you have watched Julia Roberts' Eat, Pray, Love - I'm sure you are aware of the famous Italian phrase 'Il Dolce Far Niente'- which means 'the sweetness of doing nothing'. It is believed to exist since the 18th century, and this phrase pertinently embodies the Italian lifestyle. Apart from the Italians, this concept is also no stranger to the Dutch, whose 'Niksen' is considered an art to be comprehensively practiced. The word Niksen originated from 'Niks' - Dutch for 'nothing'. Both phrases accentuate the importance of finding pleasure in doing nothing in particular but be mindful that it is far from being lazy. This concept allows you to take the time off, be idle, or simply give yourself a chance to breathe. Doing nothing could potentially do wonders for your health, and in the process, improve your life in more ways than you can imagine. Working ourselves to death, pushing our own limits to the brink of pure exhaustion will only lead to burn out, health and mental issues. This is where 'Dolce Far Niente' or Niksen plays its part, by encouraging us to contemplate, relax, and recharge to ensure the recovery of our brain function, at least for the day. In addition, it helps you to get in touch with your intuition while also releasing suppressed emotions. Learning to relax ensures the restoration of balance and enhances the possibility of discovering our most creative inner-self. Undeniably, doing nothing is indeed overwhelming as we (especially Asians) have been programmed to be productive and to feel guilty if we are not doing something. Therefore, the most crucial part of practicing this concept is by letting go of the guilt. Remember that our time is ours to make the most of. Try to disconnect and switch off from the chaotic world and if it is too much to take, start with taking only a short amount of time from your daily schedule. Here are some suggestions: =>Stare out of a window in your home =>Zone out in the bath, without any music or books =>Slot in at least one evening during the week where you don't have any plans - and just do whatever you feel like at the time, even if that's just sitting on the sofa, relaxing